Some Theories of Folklore - Nabi, Jotyar E. (Humanities Journal of University of Zakho, 2017)
Folklore is the identity of nations of the world and it is a tradition whose value keeps increasing because every school has its own system and regulations by which research can be conducted. Therefore, many different schools and theories emerged like the ones we have pointed out in this study which have their perspectives on folklore. Most of these viewpoints do not go with the contemporary scientific standpoints thus they got undermined and in place of which some more modern theories came out. Thus, in this study we attempt to point out and introduce some classic and modern theories that will be discussed.